Pilgrimage Tourism: Potentiality and Trend in Nepal - Gurung, Dhal Bahadur (Karnali Outlook: Knowledge Across Disciplines, 2026)
The study examines recent trends, potential, key destinations, and emerging dynamics of pilgrimage tourism in Nepal using secondary data from Nepal Tourism Statistics 2024, National Population and Housing Census. (2021), academic journals, news articles, and relevant literature. Finding show that pilgrimage tourism remains a significant and steadily expanding sector of Nepal driven by the rich religious diversity of sacred sites of different Hindu deities, tribal deities, Buddhists monasteries, stupas, ritual practices, and dedicated spiritual practice centers such as Lumbani, Pashupatinath, Janakpurdham, Muktinath and Halesi etc. Although the 2015 earthquake and the COVID-19 pandemic caused sharp declines, the sector demonstrated strong resilience with rapid recovery beginning in 2022 and nearing pre-pandemic levels by 2024. Increasing domestic mobility, cross-border flows, particularly from India and role of Nepal as a transit corridor for Mount Kailash-Manasarovar further strengthen its growth potential of pilgrimage tourism. However, there are many challenges such as inadequate infrastructures, weak site management, poor tourism-friendly policies, safety issues and political instability that continue to hinder sustainable tourism development, so if government addresses such challenges to provide quality facilities and link nature and religious-cultural diversity can maximize pilgrimage tourism potential in Nepal.